2010
DOI: 10.1016/j.parint.2010.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Opisthorchis viverrini excretory/secretory products induce toll-like receptor 4 upregulation and production of interleukin 6 and 8 in cholangiocyte

Abstract: Biliary tract infection with the Group I carcinogenic liver fluke Opisthorchis viverrini is associated with severe inflammation leading to cholangiocarcinoma – a major biliary cancer in Southeast Asia. However, mechanism(s) by which the liver fluke induces host mucosal immune/inflammatory responses are unclear. In the present study we address whether a normal immortalized human cholangiocyte cell line (H69 cells) recognizes and responds to O. viverrini excretory/secretory products (OVES). Expression of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 32 publications
2
68
1
Order By: Relevance
“…The bacterium Helicobacter pylori secretes cag A, a virulence factor whose uptake by epithelial cells can result in gastric cancer (Hatakeyama, 2004). Given that Ov ES products induce severe inflammation by up-regulation of cholangiocyte Toll-like receptor (TLR)4 mRNA expression, thereby promoting IL6 and IL-8 production (Ninlawan et al, 2010), it is reasonable to assume that internalized Ov ES products also promote a tumorigenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterium Helicobacter pylori secretes cag A, a virulence factor whose uptake by epithelial cells can result in gastric cancer (Hatakeyama, 2004). Given that Ov ES products induce severe inflammation by up-regulation of cholangiocyte Toll-like receptor (TLR)4 mRNA expression, thereby promoting IL6 and IL-8 production (Ninlawan et al, 2010), it is reasonable to assume that internalized Ov ES products also promote a tumorigenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Opisthorchis viverrini metacercariae were obtained from naturally infected cyprinoid fish captured from an endemic area in Khon Kaen province, north-eastern Thailand, as described previously (Ninlawan et al, 2010). Briefly, fish were digested with pepsin-HCl, and after several washes with normal saline, metacercariae were collected, identified under a dissecting microscope and used to infect hamsters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, elevated O. viverrini specific interleukin-6 (IL-6) production has been reported from peripheral blood mononuclear cells from infected individuals with advanced periductal fibrosis and CCA (Sripa et al, 2009;Sripa et al, 2012b) as well as cholangiocytes cocultured with O. viverrini excretory-secretory products (Ninlawan et al, 2010). This pro-inflammatory cytokine may potentiate the proliferation and survival of cholangiocytes within local microenvironment (Sripa et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…In human studies, elevated levels of IL-6 were found in PBMCs stimulated by O. viverrini excretory/secretory (ES) products (12) and in plasma (13) of opisthorchiasis patients with advanced periductal fibrosis. Moreover, treatment of a normal immortalized human cholangiocyte cell line with O. viverrini ES products also increased the expression of Toll-like receptor 4 (TLR-4) and subsequently stimulated the production of IL-6 and IL-8 (14). In addition, not only cytokines/chemokines but also other molecules, such as the protein peroxiredoxin 6 (Prdx6), a key regulator of the cellular redox balance, might play a role in host defense against O. viverrini infection (15).…”
mentioning
confidence: 99%